Clinical practice for outpatients that are chronically red cell dependent: A survey in the Netherlands. Issue 4 (12th December 2021) - Tonino, Rik P. B.; Schipperus, Martin R.; Zwaginga, Jaap Jan
Abstract: Background and Objectives: Limited data are available to guide physicians on how to determine the red blood cell (RBC) transfusion regimen in chronically transfusion‐dependent patients. The lack of clarity on thresholds and targets to be used for transfusion could easily result in either under or over transfusion in these patients. The aim of our survey is to investigate (1) transfusion thresholds; (2) number of RBC units given per transfusion episode; (3) interval between transfusions and (4) patient factors, like decreased cardiac function modulating the former. Materials and Methods: We sent a web‐based 44‐question survey to members of the Dutch Haematology Association. Results: Fifty physicians responded between June and October 2020 (response rate 30%), well‐distributed between community and academic hospitals. A wide variation in transfusion strategies was reported: Most patients have transfused 1–2 RBC units (range: 0–3 units) every 2–4 weeks (range: 1–12 weeks) with a median threshold of 8.0 g/dl ranging from 6.4 to 9.6 g/dl. Patient‐specific clinical factors that are most frequently reported to influence the transfusion strategy are angina pectoris, cardiac failure and dyspnoea, softer parameters that are of influence are the quality of life and self‐sustainability. Conclusion: The results of this survey indicate a broad variation in RBC transfusion strategies in Dutch patients with chronic transfusion dependency. While the current variation in transfusion strategies may be unavoidable in an individualized approach, randomized trials and better defined usable parameters to evaluate the effect of transfusion strategies are required to reach a consensus on how to determine the transfusion strategy.